2020
DOI: 10.1002/ptr.6699
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone reverses the epithelial‐mesenchymal transformation process and attenuates bleomycin‐induced pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fibrotic interstitial pneumonia that causes pulmonary tissue damage and functional impairment. To investigate the effects of cryptotanshinone on pulmonary fibrosis, the expression of NIH/3T3, HPF, and rat primary pulmonary fibroblasts was measured and found to be inhibited by CPT in a timeand concentration-dependent manner, and the upregulation of α-SMA expression in NIH/3T3 and HPF cells, which had been stimulated by TGFβ-1, was decreased after CPT administration. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…For instance, EMT and glomerulosclerosis in rats with chronic kidney disease were suppressed by JAK/STAT signaling pathway ( Zhao et al, 2019 ), and cyclosporine-A-induced renal fibrosis was ameliorated by chrysin by the inhibition of TGF-beta-induced EMT ( Nagavally et al, 2021 ). In addition, the PI3K-Akt signaling pathway, a major regulator of anti-inflammation, has been reported to prevent renal fibrosis by attenuating renal tubular epithelial cell–mesenchymal transition ( Hu et al, 2021 ; Zhang Q et al, 2020 ; Wang et al, 2019 ). In line with this, JPYSF inhibited the inflammation via suppression of the NF–kappa B signaling pathway ( Lu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, EMT and glomerulosclerosis in rats with chronic kidney disease were suppressed by JAK/STAT signaling pathway ( Zhao et al, 2019 ), and cyclosporine-A-induced renal fibrosis was ameliorated by chrysin by the inhibition of TGF-beta-induced EMT ( Nagavally et al, 2021 ). In addition, the PI3K-Akt signaling pathway, a major regulator of anti-inflammation, has been reported to prevent renal fibrosis by attenuating renal tubular epithelial cell–mesenchymal transition ( Hu et al, 2021 ; Zhang Q et al, 2020 ; Wang et al, 2019 ). In line with this, JPYSF inhibited the inflammation via suppression of the NF–kappa B signaling pathway ( Lu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our initial observations revealed that COPD was accompanied with promoted cell migration and invasion, decreased E-cadherin expression, the ratio of CD3 + , CD4 + , CD8 + and CD4 + /CD8 + T lymphocytes, and levels of IgG, IgA, and IgM, and elevated N-cadherin expression and levels of IL-6 and TNF-α. An autoimmune component related to bronchial epithelial cell damage is possibly implicated in COPD progression and the presence of IgG and IgA is involved in COPD (Zhang et al 2020 ). A recent study has also proved that ETM is a leading factor for COPD with decreased E‐cadherin expression and elevated levels of α‐SMA and collagen type I (Wang et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these core components, quercetin, betasitosterol, baicalein, luteolin, ellagic acid, wogonin, naringenin, tanshinone IIa, stigmasterol, and cryptotanshinone from DS, TR, CS, TD, QG, and MHD in FXF were the most significant in line with the degree values. Some of them were suggested previously to postpone pulmonary fibrosis course and improve the symptoms [40][41][42][43]. Besides, PTGS2, NOS2, CDK2, GSK3B, CCNA2, PPARG, MAPK14, CASP3, BCL2, and RELA ranked the top 10 places based on the degree value.…”
Section: Selection Of Core Targets In Fxf For the Treatment Ofmentioning
confidence: 99%